2021
DOI: 10.1101/2021.09.02.21262832
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The lost microbes of COVID-19: Bifidobacterium, Faecalibacterium depletion and decreased microbiome diversity associated with SARS-CoV-2 infection severity

Abstract: Objective: To compare gut microbiome diversity and composition in SARS-CoV-2 polymerase chain reaction (PCR)-confirmed positive patients whose symptoms ranged from asymptomatic to severe versus PCR-negative exposed controls. Design: Using a cross-sectional study design, we used shotgun next-generation sequencing (NGS) to evaluate microbiome composition and diversity in both patients with SARS-CoV-2 PCR-confirmed infections presenting to Ventura Clinical Trials for care from March 2020 through January 2021 and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…One study has reported a decline in Faecalibacteriumprausnitzii in COVID-19 patient gut micro ora samples [78], while the other included study reported an increase in this genus [42]. Similarly, a signi cantly lower abundance of Faecalibacterium among COVID-19 patients was reported by Hazan et al, who also reported that the increase of Faecalibacterium genus and F. prausnitzii species was inversely associated with SARS-CoV-2 positivity and COVID-19 severity [132]. In addition, many studies have linked Faecalibacterium decrease to COVID-19 severity [38,117].…”
Section: Dysbiosismentioning
confidence: 81%
See 1 more Smart Citation
“…One study has reported a decline in Faecalibacteriumprausnitzii in COVID-19 patient gut micro ora samples [78], while the other included study reported an increase in this genus [42]. Similarly, a signi cantly lower abundance of Faecalibacterium among COVID-19 patients was reported by Hazan et al, who also reported that the increase of Faecalibacterium genus and F. prausnitzii species was inversely associated with SARS-CoV-2 positivity and COVID-19 severity [132]. In addition, many studies have linked Faecalibacterium decrease to COVID-19 severity [38,117].…”
Section: Dysbiosismentioning
confidence: 81%
“…In general, Bi dobacterum reduces cell injury by inhibiting TNF-α and macrophages by enhancing Treg response [131]. Similar studies also reported a decline in Bi dobacterium of COVID-19 patients' gut microbiome and concluded that this decline would cause a reduced immune function, thus will result in a symptomatic SARS-Cov-2 infection [132]. All this information emphasizes the vital effects of this genus in regulating the immune system and outlines that its decline among COVID-19 patients would have detrimental impacts on the prognosis and severity of the disease.…”
Section: Dysbiosismentioning
confidence: 88%
“…SARS-CoV-2 infection has been reported to induce nasopharyngeal fungal microbiome dysbiosis with significant differences in microbiome diversity between COVID-19 patients and healthy individuals wherein Saccharomyces cerevisiae, Candida albicans, Candida glabrata, Aspergillus flavus, Aspergillus fumigatus, Phaffia rhodozyma and Paecilomyces variotii are the predominant fungal pathogens found in the infected patients (113,114). Moreover, studies have found a significant association between the gut/intestinal microbiome alterations and disease severity in the COVID-19 patients, with commensal microorganisms being underrepresented (115,116).…”
Section: Sars-cov-2 and Microbiotamentioning
confidence: 99%
“…SARS-CoV-2 infection changes the active respiratory microbiota, characterized by reduced alpha-diversity, and significantly lower microbial diversity (113). Resultantly, gut microbiota dysbiosis was observed to cause elevated levels of opportunistic pathogens, Streptococcus, Rothia, Veillonella, Actinomyces and a decreased number of beneficial symbionts, Blautia, Rombontsia, Collinsella, and Bifidobacterium (116).…”
Section: Sars-cov-2 and Microbiotamentioning
confidence: 99%
See 1 more Smart Citation